CGIAR Gender Researchers Leadership and Mentoring Program Post-program assessment - Njuguna-Mungai, Esther (International Livestock Research Institute, 2024)
The aim of this assessment is to capture the short-term outcomes, successes, challenges, and shortcomings of the CGIAR Gender Researchers Leadership and Mentoring Program one year after the program’s close. The lessons learned from this assessment can be used to improve future iterations of this and other similar programs in terms of content and form, to accelerate positive impacts on the leadership capacities of gender researchers globally, and thereby on the representation of critical gender issues in agenda-setting at scale.